If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(-5+n)+3n=0
We simplify the equation to the form, which is simple to understand
-5(-5+n)+3n=0
Reorder the terms in parentheses
+(+25-5n)+3n=0
Remove unnecessary parentheses
+25-5n+3n=0
We move all terms containing n to the left and all other terms to the right.
-5n+3n=0-25
We simplify left and right side of the equation.
-2n=-25
We divide both sides of the equation by -2 to get n.
n=12.5
| 2(x-14)+34=x+3x+3(x+4) | | 7x+13=8x+2 | | 3(3x-1)=-2(X+3) | | 5x^2=34x+7 | | 2x-3x-7=18 | | y=3ln(2x-3) | | 11x+14=13x-4 | | X+(y-z)= | | -24x+7=3(4-8x)-5 | | 2(10x-2)=12x+2x+5+6x-27 | | 14k+2(5k-6)=-3k-39 | | -5x+2(1-7x)= | | -3(2s-2)-6=-2(6s+4)-3 | | 5x=100x | | (xy)dx+(2x^2+3y^2-20)dy=0 | | 5z=1.1+5.9 | | 8x-3x-102=-8x+39 | | 4x-4-3y+0=0 | | 5x-2x+3=3x-1+24 | | -7(4x+7)=-28x-49 | | x-2*((-x)-2)=5 | | 6b+7=8b-13 | | 10x+11=11x+1 | | 3z+3=8z-14 | | x^2+y^2-2x-16y+65=81 | | 88+.84x=x | | 5(6r-1)+5r= | | 5(-4n-3)=-55 | | 5x-2x=3x-2 | | 10x-2x-60=-10x+36 | | y=3ln(2x-3)+x^2 | | 12u^2-13u+3=0 |